PTBP1 promotes IRES-mediated translation of cyclin B1<?A3B2 ACK?>in cancer - Fan Xinyi; Zhao Zitong; Ma Liying; Huang Xuanlin; Zhan Qimin; Song Yongmei (Acta Biochimica et Biophysica Sinica)
Cyclin B1 is an essential cyclin-dependent protein that involves in the G2/M transition. Multiple studies report that cyclin B1 is upregulated in cancers and promotes cancer progression. However, the mechanism of cyclin B1 upregulation remains unclear. Here we report that the 5′UTR of cyclin B1 mRNA contains an internal ribosome entry site (IRES) by using a bicistronic fluorescent reporter. We show that IRES can initiate the translation of cyclin B1, and the IRES-mediated translation is further activated under cell stress. Interacting trans-acting factors (ITAFs) are required by most IRES to initiate the translation. We find that PTBP1 promotes the IRES-mediated translation of cyclin B1 by binding to the 5′UTR of cyclin B1. On top of that, PTBP1 promotes the malignancy of ESCC cells. Our data suggest that the IRES-mediated translation of cyclin B1 plays an essential role in the cyclin B1 upregulation in cancers.